The Architectural Features of the Abidin Pasha Tomb - Nacide Öter (Art-Sanat)
Abidin Pasha was a statesman who has served as a sanjak manager for many years in many cities and undertook important duties during the Ottoman period. Pasha, who died in 1906, was buried in his tomb in the graveyard of Fatih Mosque. The tomb is located in the south of Gazi Osman Pasha Tomb, reflects the style of the 1st National Architecture. The baldachinshaped, square-planned building is covered with an eight-segmented dome. Baldachin-style tombs, which we encountered in the early Ottoman period, were preferred building forms not only in Anatolia but also in the Balkans during the Ottoman period. The segmented form of the dome is a rare feature in Turkish Islamic art. The examples with a dome inside and a hat outside in the previous centuries were replaced with domes both inside and outside ones in the Ottoman period. The tomb, which is completely made of marble, has two burial graves in which are also enclosed with marble. The grave in the southeast direction belongs to Veysel Pasha. Veysel Pasha, who was the brother of Abidin Pasha, also worked as a government official during the Ottoman period. The tomb, which contains the artistic elements of the period that it was built in, is also like the ancient monumental tombs in design. In this study, the plan and architectural features of the tomb were examined, and its similarity with the mausoleum in Milas Gümüşkesen was revealed.